Mоделювання коливань ділянки трубопроводу з урахуванням пружної взаємодії з рухомим інтелектуальним поршнем - Теслюк, Василь; Харченко, Лідія (КІНПАТРІ ЛТД, 2013)
We consider the bending vibration of aboveground pipeline section under moving intelligent piston. The mathematical model is based on the method of generalized displacements considering compliance of support structures, multi-section structure of the diagnostic device and elastic interactions of its elements with a pipe. As a result, we investigated the influence of the velocity of the intelligent piston on the vibrations of mechanical systems.
Modelling of vibrations of pipeline section considering elastic interactions with moving intelligent piston